ELECTORAL PROPAGANDA IN THE DIGITAL AGE: LEGAL LIMITS AND REGULATORY CHALLENGES (CIPEEX, 2025)
Technological advances and the rise of social media have transformed electoral campaigning, which was once restricted to traditional media, expanding its reach and political participation. However, this evolution has brought legal and regulatory challenges, such as the spread of disinformation, the use of algorithms for voter targeting, and the lack of transparency in campaign financing.In Brazil, particularly during the 2018 elections, these factors impacted the democratic process, highlighting the need to rethink the limits of digital electoral advertising to balance freedom of expression with the integrity of the electoral process.This study aims to analyze the legal limits and regulatory challenges faced by digital electoral advertising in Brazil. A qualitative, exploratory, and descriptive approach is adopted, using the legal-deductive method. The research is based on bibliographic and documentary analysis of legislation such as the Federal Constitution, the Electoral Code, Law No. 9,504/1997, and Law No. 13,488/2017, as well as resolutions from the Superior Electoral Court (TSE).The results show that the introduction of electoral propaganda on digital platforms has expanded the reach and interaction between candidates and voters, but it has also intensified problems such as the spread of fake news and the misuse of algorithms for targeting. The 2018 elections demonstrated the impact of these practices on Brazilian democracy, leading the Superior Electoral Court to adopt measures such as partnerships with social networks and programs to combat misinformation.Despite the advances, difficulties remain in quickly identifying and removing illicit content, which highlights the need for stronger regulations and media literacy to strengthen conscious political participation.It is concluded that, despite legislative advances and actions by the Superior Electoral Court, digital electoral propaganda still faces challenges such as fake news and limited oversight. Therefore, it is essential to invest in effective regulation and media literacy to preserve the integrity of the democratic process.
Keywords: social media; electoral law; electoral; internet; electoral advertising